Service per Conception, Conception Rate, Calving Rate and Non-Return Rate in Beef Cattle in Kalipuro, Banyuwangi - Dinul, Ahmad Rajul; Restiadi, Tjuk Imam; Wibawati, Prima Ayu; Ratnani, Hermin; Saputro, Amung Logam; Prastiya, Ragil Angga (Universitas Airlangga, 2022)
This study aimed to determine the number of reproductive efficiency parameters including service per conception, conception rate, calving rate, and non-return rate for broilers in Kalipuro District, Banyuwangi Regency. The secondary data was collected from the Banyuwangi District Agriculture Office. This research is also intended to dissect factors related to the S/C, CR, CvR, and NRR figures with descriptive analysis, including bio reproduction mastery factors, service factors, and feed factors. The primary data was collected from beef cattle breeders in Kalipuro District, Banyuwangi Regency. In addition, there were IB implementation factors whose data were obtained from questionnaires to inseminators in Kalipuro District, Banyuwangi Regency. The number of S/C broilers in Kalipuro Subdistrict, Banyuwangi Regency was good maintenance, in January-March 2020 of 1.71, 1.99, and 1.74, meanwhile, the number of CR were 58%, 50% 57%, CvR for January-March were 44%, 84%, 53% and NRR for January, February and March were 41%, 49%, and 46%, respectively, were below the standard rate.